Theme of Some Scholars’ Views RegardingWomen Education in Islamon You Tube Videos - Mahmood, Dr. Tariq (The journal of contemporary issues in business and government, 2021)
This paper presents analysis of scholars’ views about women education in Islam. The purpose of this paper is to highlight the real status of women education in religion Islam so that, those people consider Islam as a conservative; they could understand the reality about Islam. The fact is that Islam not only provided rights first from all other religion but it also promoted the status of woman in the societies. Anyhow, importance of education in Islam may be imagined from this, the first revelation was started with the word ‘ Iqra’ (read) but unfortunately followers of Islam are lack behind in field of education. Therefore, in this paper, rather than written material, spoken words of different scholars are analyzed to present Islamic point of view regarding women education. Most of scholars opine that women education is important than education for boys. But boys are preferred more for education than education for girls. Anyhow, in this, some scholars have stated that worldly education of high level institutions is the preference of the rich while the children of the poor read in religious madaris or government, Urdu medium institutions. This is why the difference between two types of qualified persons is increasing day by day especially in job markets also where educationists of Urdu medium remain lack behind than the English medium qualified educationists. Anyhow, this paper presents theme of scholars’ views regarding women education in the light of Islamic teachings and the importance of women education for family and society building and reasons of backwardness in present era especially in the education sector. In short, this paper elaborates the real picture of Islamic teachings regarding women education in the light of some famous/ eminent scholars for inhabitants of Muslim countries is proposal to stress for women education for improving their standard.